Collectivism-Based Travel Culture as the Antecedents of Travel FOMO And Intention to Travel Responsibly - Harahap, Dian E.; Arief , Mts.; Furinto, Asnan; Anggraeni, Adilla (Journal of Ecohumanism, 2024)
As collectivists, Indonesians tend to travel with friends and family. The destination is usually inspired by social media content which then will increase fear-of-missing-out anxiety (FOMO) for traveling because it generates travel intention. A previous study claimed that collectivist culture has a strong correlation with FOMO behavior. This research analyzes the role of collectivism-based travel culture as the antecedent of travel FOMO on Indonesian domestic tourists. High travel intention may lead to high profits for tourism businesses, but the sustainability of the natural habitat of the natural tourism destinations is no less important. Tourists must also increase their intention to travel responsibly when visiting natural destinations to protect nature. This study employed an empirical quantitative research method with 340 sample data of Indonesian domestic tourists. The analysis of statistical data analysis is provided from PLS-SEM. This research is limited to collectivist behavioral observation of Indonesian domestic tourists to natural tourism destinations. Future studies can be conducted on different cultural dimensions and tourism market segmentation. The analysis showed that the collectivism-based travel culture of Indonesian tourists had positive influences on both travel FOMO and intention to travel responsibly individually, but will bring damage if combined.